Mapping the Potential Liquefaction Area in Yogyakarta City Based on Ground Shear Strain Data - Ilham Ilham; Urip Nurwijayanto Prabowo; Sismanto Sismanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
The appearance of liquefaction phenomena in some places in Yogyakarta city due to the 2006 earthquake indicates that the sediment in this area has a high potential to liquefy. Three main factors that caused liquefaction are ground shaking, lithological conditions, and groundwater depth. This study aims to investigate one of the three factors i.e ground shaking. For this purpose, the ground shear strain (GSS) data were analyzed for mapping the potential liquefaction area in Yogyakarta city. They were calculated from the seismic vulnerability index and PGA. The seismic vulnerability index was analyzed from a microtremor single station data recorded in 110 sites while PGA was calculated using a reference of the 2006 earthquake. The GSS value in the study area is at a range of 2.0 × 10−4 to 5.8 × 10−3 . In this range, the soils begin to be elastic-plastic so that they are susceptible to be fracture and settlement. The high GSS correlates with the location of the liquefaction due to the 2006 earthquake. The liquefaction potential map was obtained by comparing the GSS with liquefaction sites. The high liquefaction potential is located in the southern part of Yogyakarta city covering Mantrijeron, Mergangsan, Pakualaman, Umbulharjo, and Kotagede districts.